Reformasi Birokrasi Di Indonesia, Sebuah Tinjauan Literatur - Gugun Geusan Akbar; Widaningsih Widaningsih; Novianita Rulandari (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
This article presents a review of the latest literature on Bureaucratic Reform in Indonesia and explores the development and changes of bureaucratic reform studies. This review includes 249 articles published in the Journal in the period 1998 to 2020. First, we conducted a bibliometric analysis that highlighted various matters regarding articles published in journals; second, we conducted a literature review that identified context, content, process, results, and topic changes. Our findings concentrate on the lack of detail about change processes and outcomes and the gaps between general theories used to study evolution. We propose an agenda for the study of bureaucratic reform of public organizations that focuses on its complex nature by building theoretical bridges and undertaking more in-depth empirical and comparative studies of change processes.